Faktor-faktor yang mempengaruhi tingkat kebugaran lanjut usia penghuni Panti Budi Agung Kupang di Kota Kupang - Agustina Setia; I Dewa Putu Pramantara; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: A major physiological change during aging is decreasing need of energy which occurs as a consequence of decreasing lean body mass and physical activity. This process affects absorption level. Nutrition has an important role in improving physical fitness, preventing degenerative diseases, and minimizing dependence. Decreasing fitness among the elderly may be overcome through physical exercise, sufficient nutrient intake, autonomy and mobility in undertaking daily activities.Objective: To find out factors related to fitness of the elderly at Budi Agung Charitable House, Kupang.Method: The study was observational with cross sectional design. Subject of the study based on inclusion criteria were the elderly aged more than 60 years old, could do daily activities, had no acute diseases. Exclusion criteria were those who had heart disease, lung disease, cognitive disorder, and mobility disorder. Data of nutrient intake were obtained from food record processed with computer program. Data of nutrition status were measured with body mass index, haemoglobin level with cyanmethemoglobin, and daily activities with functional independence measurement. Fitness level was measured using 6 minute-walk test. Data were analyzed using Pearson correlation and multiple regression test.Results: The study showed that there were 10 variables significantly related to physical fitness of the elderly, i.e. energy intake (p=0.009, r=0,368), protein intake (p=0.012, r=0.354), carbohydrate intake (p=0.036, r=0.297), vitamin B intake (p=0.000, r=0.691), vitamin D intake (p=0.001, r=0.455), folic acid intake (p=0.005, r=0.394), iron intake (p=0.000, r=0.540), age (p=0.002, r=-0.428), haemoglobin level (p=0.003, r=0.410), activities of daily living (p=0.000, r=0.800), but intake of fat and vitamin B were not. Body mass index statistically had no significant relationship (p>0.05) with elderly fitness level. Multiple regression analysis showed that the most influential variables that made the elderly unfit were protein intake (p=0.012 and B= -3.730), vitamin B intake (p=0.000 and B=10.352), folic acid intake (p=0.045 and B=7.085), activities of daily living (p=0.000 and B=8.014).Conclusion: High protein intake, vitamin B intake, folic acid intake, and activities of daily living increased physical fit- ness of the elderly at Budi Agung Charitable House, Kupang.